The importance of creativity and innovation in contemporary education - Farias, Eliana Santos de; Pérez-Barreira, Susana Graciela; Delou, Cristina Maria Carvalho; Wechsler, Solange Muglia (Farol, 2024)
Creativity and innovation have proven to be fundamental pillars in the current educational scenario. More than ever, it is essential to stimulate students’ imagination and divergent thinking, preparing them to face the challenges of a world in constant transformation. In education, creativity manifests itself through pedagogical practices that encourage experimentation, collaboration and problem-solving in original ways. Innovation, in turn, drives the creation of new teaching methodologies, the use of disruptive technologies and the constant adaptation of curricula to create value and meet the needs of the 21st century. Together, creativity and innovation are considered essential skills of the 21st century and must be cultivated and stimulated by a dynamic and inspiring educational environment, where students become not only passive recipients of knowledge, but also active agents in the construction of their own learning and in the search for innovative solutions to the challenges faced by society in an era of globalization.